(3TQM eNJUQ GdCNVQjs - (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s
(3ChdgG (B:s
(3bHd GdcdGe Ydi GdTQM hJMJhj Ydi CQHYI aUhd GdChd aj TQhW GdYde hGdKGfj aj TQhW GdoeJYde s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs